A simple method using anesthetics to test effects of sleep-inducing substances in mice - Hiroki Murai; Hiroto Suzuki; Hirochi Tanji; Tomoki Kimura; Yoshinori Iba (Elsevier, 2020)
We investigated the effects of sleep-inducing agents with different mechanisms of action on the loss of the righting reflex induced by isoflurane or a mixture of medetomidine, midazolam, and butorphanol (MMB), followed by atipamezole reversal. Chlorpromazine and brotizolam delayed recovery from both types of anesthesia, whereas the melatonin receptor agonist ramelteon had no effect. The orexin receptor antagonist suvorexant delayed recovery from anesthesia only in the case of MMB, while the sleep-promoting supplement glycine only delayed recovery in the case of isoflurane. These results suggest that the simple comparison method is applicable for testing substances expected to exert sleep-inducing effects. Keywords: Hypnotics, Anesthesia, Method